Lack of ‘Will’ or ‘Options’: A Study on the International Court of Justice’s Tryst With Racial Discrimination - Alexander, Atul (Indonesian Journal of International Law, 2022)
The practice of racial discrimination is detrimental to the international community’s interest. Therefore, efforts at the national and international levels to curb racial discrimination must be undertaken. The Convention on the Elimination of the Racial Discrimination (ICERD), 1969, is one such effort to curb the practice of racial discrimination. The mandate to interpret and settle disputes pertaining to racial discrimination is upon the Committee on the Elimination of Racial Discrimination (CERD). However, the CERD is endowed with functions with a limited mandate; therefore, since 2010, States have been increasingly taking recourse to inter-state dispute settlement mechanisms, i.e., the International Court of Justice (ICJ) on racial discrimination. To date, the ICJ has confronted ICERD in four contentious cases. Most of the previous research on the ICERD vis-à-vis ICJ relates to the discrete cases; however, this paper comprehensively evaluates the contribution of ICJ in interpreting the ICERD (in contentious cases). Albeit racial discrimination is one of the most heinous crimes that shakes the conscience of humanity, it is observed that the ICJ has offered chequered and circumscribed interpretation on ICERD, thus departing from ensuring ‘legal certainty’. This study also assumes significance as it sketches the ICJ’s attitude in dealing with human rights matters, transcending its pure traditional state-centric mandate.